A demographic study of urolithiasis in patients attending tertiary urological hospital in Dibrugarh, Assam, India - Sandilya, Prakritee; Sandilya, Prakritee (International Journal of Research in Medical Sciences, 2019)
Background: Urolithiasis is a common disease entity seen in medical practice. Various studies from different areas of the world indicates higher male preponderance. Our study was done to find out the gender, age and area of distribution of Urolithiasis in a tertiary urology centre in upper Assam. Methods: Our study was a retrospective study done between January 2018 to June 2018. Data was collected from the records. A total of 1041 patients were examined during this period, out of which 307 patients were diagnosed and treated for urolithiasis. Results: Out of 307 patients, 228 were males and 79 were females. Male to female ratio was 2.9:1. The maximum number of patients in the age group was between 30-39 years. Majority of the patients were from the Dibrugarh district of upper Assam. Most of the positive urolithiasis cases was fund in patients consuming a non-vegetarian diet. Conclusions: Urolithiasis is a disease with preponderance in adult males. Geographical distribution, age and diet are factors that affect the occurrence of the disease.